Curriculum Management in Elementary Schools Based on Character Education - Handayani, Neti; Ahmad, Syarwani; Indrawati, Wahyu (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
The purpose of this study is to examine character education-based curriculum management in schools. The approach employed is a qualitative. Data gathering methods include interviews, documentation, observation, and a review of the literature. Data analysis was descriptive qualitative, using Miles and Huberman's theory, including data collection, data reduction, data presentation, and conclusion. According to the findings, curriculum management that focuses on accomplishment in line with student’s character development may be carried out thoroughly and has an influence on the development of students' emotive, cognitive, and psychomotor elements. Curriculum management based on practice-based character education and habituation can provide educational institutions with a new option for executing educational activities.